The so-called food bridges: solidarity, fight against food waste and Human rights - Ibáñez-Zamacona, María Eugenia; Rebato, Esther; Escajedo San-Epifanio, Leire (Revista de Antropología Social, 2021)
The coexistence between high rates of food waste and an increasing number of people in food insecurity is one of the paradoxes of the contemporary food system. The so-called food bridges are strategies that, driven by different actors, seek to ensure that perfectly edible food that have been left out of the commercial circuit can be redirected towards people who are in a situation or at risk of social exclusion. In some cases, these strategies have not arisen from a desire to serve people who are in a situation or at risk of food insecurity, but rather from the need to dispose significant amounts of food surpluses, and even with the intention to access the fiscal and social benefits associated with food donations. Thus, issues such as the impact that this type of practices have on food recipients and the compatibility of some donation models with formulas of social intervention that are aimed at developing people’s autonomy are relegated to a secondary position. After an analysis of food surplus recruitment and donation strategies that are active in different areas of Spain, this work analyses, from a Human rights perspective, the lights and shadows of this type of strategies in short, medium and long term